Tathwîr al-Mawâd at-Ta’lîmiyyah li Mahârah al-Istimâ’ bi-Istikhdâm Plotagon Studio - Zulfanuria, Alfin Khoiri; Asy’ari, Hasyim (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
This study aimed to develop the listening skills teaching materials using the Plotagon Studio for class VII students of MTs Hikmatul Amanah Mojokerto and to determine the effectiveness of it. The type of this research was Research and Development (R&D) by adopting the ADDIE development model comprised of five stages including (Analyze, Design, Development, Implementation, and Evaluation). The data collection techniques were observations, interviews, questionnaires, and tests. Data analysis was carried out by the statistical program SPSS 23 with paired sample T-Test and N-Gain Score. The results showed that the listening skills teaching materials using the Plotagon Studio was considered feasible and needed by the students in learning Arabic. The precentage score of validity from the material expert was 81.25%, from the design expert was 79.5% and 90% from the linguist. The use of listening skills teaching materials using the Plotagon Studio has been proven to be effective. It was evidenced by the results of the Paired Sample T-Test obtained (Sig (2-tailed)) value<0.005 It indicated that the alternative hypothesis (Ha) was accepted. While the results of the N-Gain test showed that the score was 64.2 at the moderately effective category.